The Impact Of Ground Water Dynamics On Carbon Emission Rate Of Tropical Swamp Deposit - Triadi, L. Budi; F. Adji, Fengky; Lasmana, Yudi (JURNAL SUMBER DAYA AIR, 2018)
Drainage of peatlands will lower the water table, decompose the organics matter and increases the fire risk. Therefore knowledge of C emission rate is very important for drainage system planning, in order to preserve peat. Scientific methods that used in this study: calculation of thickness/ depth of the peat, peat volume, oxidized peat volume, C dry peat weight and CO2 equivalent. The rate of emission C is calculated on the basis of emission C and subsidence time. Furthermore, the emission rate C (Mton CO2/ yr) is calculated based on 4 (four) model/ scenario concepts, i.e: actual/ existing condition, plantation, canal blocking and canal blocking with reforestation. This activity was conducted in Sei Ahas, Kapuas, Central Kalimantan and Sungai Buluh, Tanjung Jabung Timur, Jambi. Based on research, it was found that land use change will greatly affect the change of ground water level of peat that contributes to increases the emission of C to the atmosphere.